(3GdMeGjI GdLfGFjI ddeMejGJ GdWHjYjI (B: s (3OQGSI JMdjdjI JGUjdjI ai VhA GdJTQjYGJ GdhVYjI (B/ s - (3NGdO Ydi YQGbis; (3eGehf eMeO SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3GdeMejGJ GdWHjYjI LRA gGe ef GdHjFI hYfOeG JfHg GdGfSGf Gdi GgejJg HOG ai GSHGZ GdMeGjI GddGReI Ydjg dMaXg VO GdGYJOGA Ydjg hJdhjKg hGdeMejGJ GdWHjYjI Gi eSGMI ef GdGQV Gh GdejGg GdSGMdjI Gh GdOGNdjI JJejR HeG JVeg ef cGFfGJ MjI fHGJGJ Gh MjhGfGJ Gh GSeGc Gh XhGgQ WHjYjI PGJ bjeI KbGajI Gh YdejI Gh SjGMjI Gh LeGdjI hjUOQ HJMOjOgG bQGQ ef QFjS eLdS GdhRQGA HfGA Ydi GbJQGM LgGR TFhf GdHjFI HeLdS GdhRQGA hGdhGVM ef GdJYQja Gf gPg GdeSGMGJ ef GdGQV Gh GdejGg ShGA GdSGMdjI Gh GdOGNdjI JJejR HhLhO cGFfGJ Gh fHGJGJ Gh MjhGfGJ Gh GSeGc Gh XhGgQ WHjYjI bO dG JJcQQ ai ecGf GNQ ef GdYGde hgPg GdXhGgQ dgG bjeI YGdjI ShGA KbGajI Gh YdejI Gh SjGMjI Gh LeGdjI hgfGc GdYOjO ef UhQ GdeMejGJ GdWHjYjI aGdJbSje GdeUQi dgG jfOQL JMJg YTQ UhQ ddeMejGJ GdWHjYjI Ke JUfjage MSH eG HOGNd GdeMejI ef eejRGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2006s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B255-274s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdeMejGJ GdWHjYjIs; (3GdfGMjI GdGbJUGOjIs; (3fhXja GdSjGMI ai NOeI GdHjFIs; (3GdHjFI hGdeMejGJ GdWHjYjI s; (3eMd LQGFe GdeMejGJ GdWHjYjI s; (3WQb JShjI efGRYGJ GdHjFI s; (3LhGfH GdeSFhdjI ai GdLQGFe Ydi GdeMejGJ s; (3GSGS GdeSFhdjI hGdJYhjV s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs